2013
DOI: 10.1128/jcm.00202-13
|View full text |Cite
|
Sign up to set email alerts
|

Does Neutralization of Gastric Aspirates from Children with Suspected Intrathoracic Tuberculosis Affect Mycobacterial Yields on MGIT Culture?

Abstract: The microbiological confirmation of pulmonary tuberculosis in children relies on cultures of gastric aspirate (GA) specimens. Conventionally, GAs are neutralized to improve culture yields of mycobacteria. However, there are limited data to support this practice. To study the utility of neutralization of GAs with sodium bicarbonate in children with intrathoracic tuberculosis, a total of 116 children of either sex, aged 6 months to 14 years (median age, 120 months; interquartile range [IQR], 7 to 192 months), un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 12 publications
0
7
1
Order By: Relevance
“…19 The wide difference in yield between smear and culture, in contrast to our study, was probably due to patients having early disease with minimal changes on 20 In our study, although the samples were not neutralised, the contamination rate was significantly higher in specimens with >5 ml volume, presumably because of the fluid instilled before aspiration.…”
Section: Discussioncontrasting
confidence: 83%
“…19 The wide difference in yield between smear and culture, in contrast to our study, was probably due to patients having early disease with minimal changes on 20 In our study, although the samples were not neutralised, the contamination rate was significantly higher in specimens with >5 ml volume, presumably because of the fluid instilled before aspiration.…”
Section: Discussioncontrasting
confidence: 83%
“…Samples of 5 to 10 ml are collected on 3 consecutive days, and if not processed within 4 h of collection, they should be adjusted to neutral pH with sodium carbonate since long-term exposure to acid can be detrimental to mycobacteria (10). However, one recent study reported that culture yield of nonneutralized specimens was, in fact, superior to neutralized specimens (11). Additionally, many recent studies have demonstrated that sputum can be induced from children as young as 1 month of age and that the microbiologic yield from one wellcollected induced sputum (IS) is similar to that from 3 gastric aspirates (4).…”
Section: Specimen Selection Collection and Transportmentioning
confidence: 99%
“…We have earlier reported that GA samples provide better yields than IS samples [ 19 ]. In a subsequent report we also showed that neutralizing the pH of gastric aspirate before processing leads to a higher rate of contamination without improving the detection rate [ 20 ]. In the present study we report on the performance of the Xpert MTB/RIF on archived GA and IS samples collected on two consecutive days from children with probable intrathoracic TB, recruited as part of a double blinded randomized controlled trial to study the role of micronutrient supplementation in children with intra-thoracic tuberculosis.…”
Section: Introductionmentioning
confidence: 99%